2015
DOI: 10.1016/j.bbamcr.2015.07.011
|View full text |Cite|
|
Sign up to set email alerts
|

Syndecan-4 ectodomain evokes mobilization of podocyte TRPC6 channels and their associated pathways: An essential role for integrin signaling

Abstract: PodocyteTRPC6 channels have been implicated in glomerular diseases. Syndecan-4 (Sdc4) is a membrane proteoglycan that can be cleaved to release a soluble ectodomain capable of paracrine and autocrine signaling. We have confirmed that overexpression of Sdc4 core protein increases surface abundance of TRPC6 channels in cultured podocytes, whereas Sdc4 knockdown has the opposite effect. Exposure to soluble Sdc4 ectodomain also increased the surface abundance of TRPC6, and increased cationic currents evoked by a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Syndacan-4 is required for activation of calcineurin/NFAT signaling in response to mechanical stress through TRPC6 in cardiac fibroblasts, promoting production of extracellular matrix and differentiation into activated myofibroblasts thereby increasing myocardial stiffness [233235]. …”
Section: Calcineurin Substrates Relevant To Cardiovascular Healthmentioning
confidence: 99%
“…Syndacan-4 is required for activation of calcineurin/NFAT signaling in response to mechanical stress through TRPC6 in cardiac fibroblasts, promoting production of extracellular matrix and differentiation into activated myofibroblasts thereby increasing myocardial stiffness [233235]. …”
Section: Calcineurin Substrates Relevant To Cardiovascular Healthmentioning
confidence: 99%
“…FYGL dose dependently reduced blood glucose concentration, kidney/body weight ratio, serum creatinine and urea nitrogen as well as albuminuria in diabetic mice via increasing the activities of renal superoxide dismutase, glutathione peroxidase and catalase compared to untreated diabetic mice [48]. In the same study, the decrease of renal malondialdehyde content and 8-hydroxy-2'-deoxyguanosine expression were also observed in FYGL-treated diabetic mice compared to the untreated diabetic mice, along with protects against oxidative stress by sequestering and reducing the protease activity of the apoptosis-inducing serine protease, OMI/HtrA2 [45] astrocytoma versican enhances cell attachment and expression of beta-1 integrin and fibronectin [46] Other organs podocyte syndecan ectodomain shed from syndecan-4 increases generation of ROS [47] kidney FYGL (exogenous PG) protective role against oxidative damage due to its antioxidant potential [48] serum, liver FYGL (exogenous PG) FYGL treated db/db mice had lower levels of malondialdehyde, 8-hydroxydeoxyguanosin and protein carbonyl, and significant increase in the antioxidant enzyme activities, including SOD, CAT and GSH-peroxidase, in both serum and liver [49] an amelioration of renal morphologic abnormalities [48]. In another study, FYGL showed antidiabetic, antihyperlipidemic and antioxidant effects in db/db mice [49].…”
Section: Other Organsmentioning
confidence: 99%
“…A study showed that Sdc4 ectodomain increased surface abundance of TRPC6 channels, generation of ROS, activation of Rac1, nuclear abundance of NFATc1 as well as total 3-integrin and reduced activation of RhoA in podocytes [47]. Therefore, locally generated Sdc4 might play a role in regulating TRPC6 channels, and may contribute to glomerular pathology [47].…”
Section: Other Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated fatty acid oxidation affects podocin palmitoylation and thus proper membrane insertion; fatty acid overload may cause altered lipid composition of the lipid rafts and therefore interferes with network signaling of the podocin-nephrin-TRPC-6 actin cytoskeleton, triggering a cascade of well-described downstream events that have pathologic effects. Lipids are essential for maintaining the function of renal cells, while lipid metabolism derangement induces an inflammatory reaction, oxidative stress, fibrous degeneration and necrosis on renal tissue (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%